The Influence of the Mind Mapping Model Ability to Write Expositional Text by Tenth Grade Students of SMA N 1 Pakkat - Simanullang, Andika P; Mariati Saragih (Institute of Computer Science (IOCS), 2021)
This research aims to determine the effect of the Mind Mapping Model ability to write exposition text of tenth grade SMA Negeri 1 Pakkat. The population of this study were all students of SMA Negeri 1 Pakkat with 164 students. The sampling uses random sampling technique consisting of one classnamelywith 30 students. The method in this research is experimental method with one group pre-test post-test design. The instrument used was an essay test. From data processing, obtained pre-test results with an average = 67, standard deviation = 7.44. The result of post-test mean = 80.66 standard deviation = 7.95. From the pre-test and post-test results, both results were normally distributed. From the homogeneity test it was found that the sample of this study came from a homogeneous population. After the normality and homogeneity test, the tÂ° value was obtained at 6.79 with t table at a significant level of 5% with df = N-1 = 30-1 = 29, the t table value was 2.04. These results indicate the t-count value is 6.79> 2.04, then the hypothesis (Ho) is rejected and the alternative hypothesis (Ha) isaccepted. So it can be concluded that there is an effect of the Mind Mapping Model ability to write exposition .